EKSPLORASI HASIL PENELITIAN YANG TERINTEGRASI TEKNOLOGI INFORMASI DAN KOMPUTER (TIK) DALAM PEMBELAJARAN MATEMATIKA - Viola Widone Putri; Suripah Suripah (Universitas Sultan Ageng Tirtayasa, 2021)
This study aims to explore the results of research by mathematics education students who have integrated ICT in the design of mathematics learning. This type of research is a qualitative descriptive. The data collection technique used is document observation in the form of a study of student research documents in the form of a thesis. The data used in this study is the result of the thesis research of UIR mathematics education students for the last five years (2016-2020). This study uses qualitative data analysis techniques, namely: (1) data collection; (2) data reduction; (3) data presentation; (4) raising the conclusion; and (5) data presentation. This research is focused on three aspects, namely: (1) the type of research; (2) types of learning; and (3) the type of media used. The results of this study indicate that, the results of student research during 2016-2020 in general are still dominant in not integrating ICT, obtained 19 student studies that have integrated ICT and as much as 2.4% dominant using the type of R&D research. The type of learning in student research that has integrated ICT is 2.14% dominant using multimedia-based learning. As well as research students who have integrated ICT 0.57% dominantly use ICT media in the form of Macromedia Flash and Adobe Flash.